PENGUATAN LITERASI MELALUI PEMBELAJARAN BERBASIS CERITA RAKYAT LOKAL DI KELAS 3 SD PKMI TELUKDALAM - Gaurifa, Midarwati (Universitas Nias Raya, 2024)
This community service activity aims to improve literacy among third-grade students at SD PKMI Telukdalam through local folk tale-based learning. Using an interactive approach, students are introduced to various folk tales rich in cultural and moral values. The methods employed include storytelling, group discussions, and creative activities such as story writing and drawing. The results of this activity show a significant improvement in students' reading skills and comprehension, as well as an increased interest in reading. Additionally, the involvement of parents and the community in sharing sessions enhances awareness of the importance of literacy and the preservation of local culture. This program is expected to serve as a model for similar activities in the future, with an emphasis on integrating culture into education to foster a literate generation that takes pride in their local identity.